2020
DOI: 10.1007/s10126-019-09939-1
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic Salmon (Salmo salar L., 1758) Gut Microbiota Profile Correlates with Flesh Pigmentation: Cause or Effect?

Abstract: In Tasmania (Australia), during the marine phase, it has been observed that flesh pigmentation significantly drops in summer, possibly due to high water temperatures (> 20°C). Although this deleterious effect of summer temperatures has been ascertained, there is a lack of knowledge of the actual mechanisms behind the impaired uptake and/or loss of pigments in Atlantic salmon in a challenging environment. Since the microbial community in the fish intestine significantly changes in relation to the variations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 90 publications
(82 reference statements)
4
24
0
Order By: Relevance
“…During this time, the fluctuation of water temperature is one of the reasons causing stress in fish [ 5 ] and induces feed reduction or cessation. As a result, water temperature can also affect the fish gut microbiota in Atlantic salmon, as previously demonstrated [ 6 , 7 , 8 ] and confirmed in our recent study [ 9 ], where we showed that changes in the distal gut microbiota profile correlates with flesh color variation across different time points during the relevant period (February–August). Although it is clear that overall temperature fluctuation has an impact on color loss during that period [ 3 ], flesh color variation correlation with the gut microbiota is independent of the change in water temperature [ 9 ], since fish with reduced flesh color have similar microbiota profiles in the distal gut regardless of the time point tested.…”
Section: Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…During this time, the fluctuation of water temperature is one of the reasons causing stress in fish [ 5 ] and induces feed reduction or cessation. As a result, water temperature can also affect the fish gut microbiota in Atlantic salmon, as previously demonstrated [ 6 , 7 , 8 ] and confirmed in our recent study [ 9 ], where we showed that changes in the distal gut microbiota profile correlates with flesh color variation across different time points during the relevant period (February–August). Although it is clear that overall temperature fluctuation has an impact on color loss during that period [ 3 ], flesh color variation correlation with the gut microbiota is independent of the change in water temperature [ 9 ], since fish with reduced flesh color have similar microbiota profiles in the distal gut regardless of the time point tested.…”
Section: Introductionsupporting
confidence: 90%
“…In our previous study [9], a low color index was correlated with Pseudoalteromonadaceae (F), Vibrionaceae (F) and Enterobacteriaceae (F) in the distal gut, which also dominated in the low color group in both gut regions -the distal gut and pyloric caeca -in this study (Figures 5 and 6). Despite the different seasons and environmental conditions between the two studies (the two sampling events took place 2 years apart), Pseudoalteromonadaceae (F), Vibrionaceae (F) and Enterobacteriaceae (F) still persisted in the low color index group, indicating their core position as the symbionts in the altered-symbiosis microbiota composition.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations